Safety, Tolerability, and Serum/Tear Pharmacokinetics of Human Recombinant Epidermal Growth Factor Eyedrops in Healthy Subjects - Hyounggyoon Yoo; Seonghae Yoon; In-Jin Jang; Kyung-Sang Yu; Joon Young Hyon; Jungi Hwang; Inyoung Hwang; Jung Sunwoo; Jae-Yong Chung (MDPI AG, 2022)
The purpose of this study was to evaluate the safety, tolerability, and pharmacokinetics (PKs) of rhEGF eyedrops after the administration of single and multiple doses in healthy subjects. A phase 1, randomized, double-blind, placebo-controlled, and single-ascending dose (SAD) and multiple-ascending dose (MAD) study were conducted in three dose groups (10, 50, and 100 μg/mL). The subjects randomly received rhEGF eyedrops or the placebo in a 3:1 ratio. Serial blood and tear samples for PK analysis were collected up to 36 h and 180 h post-dose in SAD and MAD studies, respectively. In addition, the serum and tear EGF concentrations were measured. Immunogenicity evaluations were conducted using serum anti-EGF antibody levels. A total of 50 subjects were enrolled and 48 subjects completed the study. Adverse drug reactions were mild and transient. There were no serious adverse events in this study. The tear EGF concentrations rapidly increased and returned to baseline after 4 h without any serum EGF level change after the administration of rhEGF eyedrops. rhEGF eyedrops were safe and well-tolerated in healthy subjects in a dose range of 10-100 μg/mL, indicating suitability for further studies in patients with corneal injury.